191,185 views
17 votes
17 votes
I need help with this ASAP

I need help with this ASAP-example-1
User Welah
by
2.9k points

1 Answer

13 votes
13 votes

Explanation:

it's really simple.

g(f(x)) means that you use x to create f(x), and then you use this f(x) as argument in g(x).

with our functions here it means in general to use f(x) = 4 - x as argument (instead of purely x) in g(x).

g(f(x)) = 5×(4 - x) - 2 = 20 - 5x - 2 = 18 - 5x

that is the whole trick.

now, when we have a specific x value (x = 6 in our example here), it can be even simpler.

we need to "feed" 6 into f(x).

4 - x = 4 - 6 = -2

so, f(6) = -2

now this -2 becomes the argument for g(x).

5×(-2) - 2 = -10 - 2 = -12

so, g(f(6)) = -12

let's check for control and also use the functional definition of g(f(x)) we established above :

18 - 5×6 = 18 - 30 = -12

the same result, so all correct.

User Sonxurxo
by
2.9k points